2013
DOI: 10.1182/blood-2013-03-491092
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of integrated genetic profiling in adult T-cell acute lymphoblastic leukemia

Abstract: Adult T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematologic tumor associated with poor outcome. In this study, we analyzed the prognostic relevance of genetic alterations, immunophenotypic markers, and microarray gene expression signatures in a panel of 53 adult T-ALL patients treated in the Eastern Cooperative Oncology Group E2993 clinical trial. An early immature gene expression signature, the absence of bi-allelic TCRG deletion, CD13 surface expression, heterozygous deletions of the short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 54 publications
6
122
5
1
Order By: Relevance
“…The fact that MEF2C is overexpressed in 30/37 (81.8%) cases (SI Appendix, Fig. S10) suggested a common disease mechanism (31). In addition, ETP cases had higher mutation rates of epigenetic factors, IDH2, DNMT3A, and EZH2 in particular, , imatinib (50 mg/kg) treated mice with ZA (n = 6), and dasatinib (5 mg/kg) treated mice with ZA (n = 6).…”
Section: Correlation Among Gene Fusions/mutations/aberrantly Overexprmentioning
confidence: 99%
“…The fact that MEF2C is overexpressed in 30/37 (81.8%) cases (SI Appendix, Fig. S10) suggested a common disease mechanism (31). In addition, ETP cases had higher mutation rates of epigenetic factors, IDH2, DNMT3A, and EZH2 in particular, , imatinib (50 mg/kg) treated mice with ZA (n = 6), and dasatinib (5 mg/kg) treated mice with ZA (n = 6).…”
Section: Correlation Among Gene Fusions/mutations/aberrantly Overexprmentioning
confidence: 99%
“…In contrast, the incidence of NOTCH1/FBXW7 mutations (47%) was lower in refractory/relapsed T-ALL than in the general unselected T-ALL population and these mutations were mostly found in combination with a second lesion in the pathway or different pathways, in line with their association with a favorable prognosis. [30][31][32][33] Moreover, we observed that NOTCH1/FBXW7 status could differ between matched diagnostic and relapse samples, indicating that NOTCH1/FBXW7 mutations might be secondary events in T-ALL.…”
Section: Discussionmentioning
confidence: 86%
“…To address this question, we analyzed publicly available databases and cross-compared the expression of CK2 subunits among subsets of developing T cells and patient T-ALL cells that are arrested at different developmental stages. 9 We found that the transcript levels of all CK2 subunits (α, α' and β) were significantly higher in patient T-ALL cells, compared to normal T cells regardless of their developmental stages ( Figure 1A and B and Online Supplementary Figure S1A). We next examined protein levels of CK2, cleaved-NOTCH1 and MYC by Western blots in a panel of primary T-ALL patient samples.…”
mentioning
confidence: 85%